Future Trading in Essential commodities in India: Beneficial Neither to Consumers nor to Farmers - Mittal , A K; Aggarwal, Vimal Kumar (Gyan Management Journal, 2011)
The main objective of Future trading in commodities is to provide an efficient and effective mechanism to manage price risk for both the parties, producers and consumers of the commodities. Future contracts should protect them against unfavorable price changes. Speculators who are neither consumers nor producers seek to profit from changes in price during the contract period. Some influential players, having large financial and other infastructure base, manipulates the essential commodity markets, resulting in sharp rise in prices in short duration, affecting the interest of common men. These manipulators extract undue benefits from insufficiently developed infrastructure end base, that is far below from the required levels for achieving the objectives of future trading in Agro commodities. Majority of farmers in India, being marginalized and illiterate, do not benefit from manipulated price rise of their agro-produce and at the same time, consumers end up in paying high retail prices.